BEHAVIOR ANALYSIS OF CONSUMER COMPLAINT - Andrie Prasetyo; Hartoyo Hartoyo; Netti Tinaprila (Indonesian Journal of Business and Entrepreneurship (IJBE), 2016)
Complaining is one form of communication for consumers to express their dissatisfaction. Understanding the consumer complaint behavior is an important thing for businesses; however, it is not easy to do. The initial step in understanding this behavior of consumer complaints is to map consumers based on their behavior of complaints and analyze the factors that influence this. This study examines the complaint behavior of consumers in Cibubur who have experienced dissatisfaction with a product.  The objectives of this study are to map the consumer complaint behavior and identify its relationship with various factors such as consumer demographics, personality, attitude to businesses, attribution of the causes of dissatisfaction, and product attributes. A crosstab descriptive analysis method was used to map the consumers, while the Pearson correlation analysis methods was used to analyze consumer complaint behavioral relationships with various factors. The results of this study indicated that consumers in Cibubur based on their complaint behavior are classified into four groups: passive, voicers, irates and activist. The passive consumers dominate the category with a percentage of 49%.  The voicers, irates, and activist belong to the complaining type and are dominated by young women, with high levels of education and income. Keywords: consumer complaint behavior, product, crosstab, pearson correlation